Berberine Relieves Metabolic Syndrome in Mice by Inhibiting Liver Inflammation Caused by a High-Fat Diet and Potential Association With Gut Microbiota - Li, Jinjin; Li, Jialin; Ni, Jiajia; Zhang, Caibo; Jia, Jianlei; Wu, Guoying; Sun, Hongzhao; Wang, Shuzhen (Frontiers in Microbiology, 2022)
Whether berberine mediates its anti-inflammatory and blood sugar and lipid-lowering effects solely by adjusting the structure of the gut microbiota or by first directly regulating the expression of host pro-inflammatory proteins and activation of macrophages and subsequently acting on gut microbiota, is currently unclear. To clarify the mechanism of berberine-mediated regulation of metabolism, we constructed an obese mouse model using SPF-grade C57BL/6J male mice and conducted a systematic study of liver tissue pathology, inflammatory factor expression, and gut microbiota structure. We screened the gut microbiota targets of berberine and showed that the molecular mechanism of berberine-mediated treatment of metabolic syndrome involves the regulation of gut microbiota structure and the expression of inflammatory factors. Our results revealed that a high-fat diet (HFD) significantly changed mice gut microbiota, thereby probably increasing the level of toxins in the intestine, and triggered the host inflammatory response. The HFD also reduced the proportion of short-chain fatty acid (SCFA)-producing genes, thereby hindering mucosal immunity and cell nutrition, and increased the host inflammatory response and liver fat metabolism disorders. Further, berberine could improve the chronic HFD-induced inflammatory metabolic syndrome to some extent and effectively improved the metabolism of high-fat foods in mice, which correlated with the gut microbiota composition. Taken together, our study may improve our understanding of host-microbe interactions during the treatment of metabolic diseases and provide useful insights into the action mechanism of berberine.